Occurrence and Variety of β-Lactamase Genes among Aeromonas spp. Isolated from Urban Wastewater Treatment Plant - Piotrowska, Marta; Przygodzińska, Dominika; Matyjewicz, Klaudia; Popowska, Magdalena (Frontiers in Microbiology, 2017)
Members of the genus Aeromonas that commonly occur in various aquatic ecosystems are taken into account as vectors spreading antibiotic resistance genes in the environment. In our study strains of Aeromonas spp. (n=104) not susceptible to ampicillin were isolated from municipal sewage of different levels of purification - raw sewage, activated sludge and treated wastewater. The crucial step of the study was the identification of β-lactamase resistance genes. The identified genes encode β-lactamases from 14 families – blaTEM, blaOXA, blaSHV, blaCTX-M, blaMOX, blaACC, blaFOX, blaGES, blaPER, blaVEB, blaKPC, cphA, imiH and cepH. There were no significant differences in number of identified antibiotic resistance genes between isolation points. BlaOXA, blaFOX variants and, characteristic for Aeromonas genus, metallo-β-lactamase cphA-related genes were the most commonly identified types of β-lactam resistance determinants. Moreover, we found four ESBL (blaSHV-11, blaCTX-M-27, blaCTX-M-98 and blaPER-4) - and seven AmpC (blaACC, blaFOX-2-like, blaFOX-3, blaFOX-4-like, blaFOX-9, blaFOX-10-like and blaFOX-13-like) types and variants of genes that had never been found among Aeromonas spp. before. Five of the β-lactamases families (blaTEM, blaOXA, blaFOX, blaVEB and cphA) were identified in all three isolation sites, which supports the hypothesis that wastewater treatment plants are hot spots of antibiotic resistance genes dissemination. The obtained antibiotic resistance genes sequences share high identity with previously described β-lactamases, but new variants of those genes have to be considered as well. Characterization of antibiotic susceptibility was performed using disc the diffusion method with 12 different antibiotics according to CLSI guidelines. Over 60% of the strains are unsusceptible to cefepime and chloramphenicol and the majority of the strains have a multidrug resistance phenotype (68%). Finally, analysis of plasmid profiles among the resistant strains showed that 62% of the isolates from all three points of the wastewater treatment plant carry plasmids of different sizes. Among some of the isolated plasmids blaFOX-4-like and blaGES genes have been found. To sum up, the results strongly suggest that Aeromonas spp. can be considered as agents of antibiotic resistance dissemination from wastewater to the natural environment.